An investigation of neuromelanin distribution in substantia nigra and locus coeruleus in patients with Parkinson’s disease using neuromelanin-sensitive MRI - Qiang Liu; Pan Wang; Chenghe Liu; Feng Xue; Qian Wang; Yuqing Chen; Ruihua Hou; Teng Chen (BMC Neurology, 2023)
Abstract Loss of neuromelanin in the midbrain is known in Parkinson’s disease(PD), which can now be directly detected by neuromelanin-sensitive MRI(NM-MRI). This case-control study was to investigate the distribution of neuromelanin in the substantia nigra(SN) and the locus coeruleus(LC) using NM-MRI technique and evaluate its potential as a diagnostic marker for PD. 10 early PD patients(H&Y stage I, II), 11 progressive PD patients(H&Y stage III-V), and 10 healthy controls matched in age and gender were recruited. All participants completed clinical and psychometric assessments as well as NM-MRI scans. Neuromelanin signal intensities in SN and LC were measured by contrast-to-noise ratios(CNRs) derived from NM-MRI scans. There were significant decreases of CNRs in SNpc(including anterior, central, and posterior) and LC in PD patients compared to controls. There were also significant differences of CNR between the left and right sides. CNR in LC had a negative correlation with the Non-Motor Symptoms Scale(NMSS) score in PD patients(|R|=0.49), whereas CNR in SNpc did not correlate with Unified Parkinson Disease Rating Scale(UPDRS) score(|R|<0.3). The receiver operating characteristic(ROC) curves revealed that the CNR in LC had a high diagnostic specificity of 90.1% in progressive patients. This study provides new evidence for the asymmetric distribution of neuromelanin in SN and the LC of patients with PD. The neuromelanin loss is bilateral and more predominately in LC than that in SN. This distinct neuromelanin distribution pattern may offer a potential diagnostic marker and a potential neuropharmacological intervention target for PD patients.